Towards Coherence In Criminal Justice (Peter Lang International Academic Publishers, 2025)
This book explores the pursuit of coherence in criminal justice, addressing how criminal laws and practices can become more rational and aligned with human rights principles. It examines key criminal justice principles like legality, proportionality, and presumption of innocence, aiming to adapt them to modern societal and technological challenges. The work highlights the growing influence of international conventions and European courts on national legal systems, emphasizing the need for thoughtful implementation of transnational precedents. While focused on Lithuanian criminal justice, topics like human trafficking, drug possession, and electronic evidence are relevant across Europe, offering insights for legal researchers globally.